Design and analysis of an asymmetrical star-shaped fractal antenna with meta-surface integration at 5.2 GHz - Dalsania, Piyush; Rathod, Jagdish M. (Bulletin of Electrical Engineering and Informatics, 2025)
Wireless communication requires optimized antenna designs to ensure maxi mum signal reception and transmission in today’s rapidly advancing technolo gies. Recent research emphasizes improving antenna efficiency and directivity to support higher data rates, extended coverage, and reliable connectivity. How ever, conventional antenna structures often suffer from narrow bandwidth, low radiation efficiency, and high return loss, which degrade signal quality and re strict operational range, particularly in complex electromagnetic environments. This study introduces an innovative asymmetrical star-shaped fractal antenna coupled with a metasurface layer consisting of periodic split-ring resonator (SRR) unit cells on a FR4 substrate to overcome these restrictions. The SRR based metasurface plays a critical role in suppressing surface waves, improving impedance matching, and enhancing radiation directivity. Experimental evalu ations were performed across 4.5–10 GHz, focusing on key performance mea sures such as gain, return loss, and voltage standing wave ratio (VSWR). The suggeted antenna achieved a stable return loss below −10 dB and demonstrated a strong operational peak at 5.2 GHz, with improved directivity and radiation efficiency compared to conventional patch designs. The integration of asym metrical star-shaped fractal geometry with SRR-based metasurface technology effectively addresses the shortcomings of traditional antennas, establishing the proposed design as a compact, efficient, and reliable candidate for mid-band wireless communication systems.